PREANALITIC AND INTERPRETATION BLOOD GLUCOSE FOR DIAGNOSE DIABETIC MELITUS - Wayan Kardika, Ida Bagus; Herawati, Sianny; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Diabetes mellitus (DM) is a metabolic disorder disease which has been characterised by chronic hyperglycemia as well as abnormalities in the metabolism of carbohydrates, fats and proteins caused by abnormalities of insulin secretion, insulin resistance or both. The Diagnoses of diabetes mellitus in addition based on the clinical aspects of which include anamnesis, physical examination and diagnoses is required in the form of investigations the laboratory examination. The simplest laboratory examination is the examination of blood sugar. The stages of preanalitic and the interpretation of results examination of the blood sugar is worth noting in order to obtain meaningful results so that a diagnosis of diabetes mellitus can be enforced and for monitoring treatment outcomes. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Diabetic Mellitus, Preanalitic, insulin